Pengaruh Iklan Media Sosial dan Ulasan Produk terhadap Keputusan Pembelian Shopee di Solo Raya - dealira juna sabdias (STIE Wijaya Mulya, 2025)
The purpose of this study is to examine how product reviews and social media advertising influence Shopee customers' purchasing decisions during Eid al-Fitr in Solo. An online survey with 00 respondents was used, using quantitative techniques. SPSS was used in the online data. Although product reviews have a positive and significant influence on purchasing decisions, social media advertising has a positive but negligible influence. Both variables account for 21% of the variation, with other factors influencing the remaining 21%, based on an adjusted R2 value of 0.210. Keywords: Shopee, product reviews, social media advertising, and purchasing decisions